Pharmacological Activities and Mechanisms of Hirudin and Its Derivatives - A Review - Chen Junren; Chen Junren; Xie Xiaofang; Xie Xiaofang; Zhang Huiqiong; Zhang Huiqiong; Li Gangmin; Li Gangmin; Yin Yanpeng; Yin Yanpeng; Cao Xiaoyu; Cao Xiaoyu; et al. (Frontiers Media S.A., 2021)
Hirudin, an acidic polypeptide secreted by the salivary glands of Hirudo medicinalis (also known as "Shuizhi" in traditional Chinese medicine), is the strongest natural specific inhibitor of thrombin found so far. Hirudin has been demonstrated to possess potent anti-thrombotic effect in previous studies. Recently, increasing researches have focused on the anti-thrombotic activity of the derivatives of hirudin, mainly because these derivatives have stronger antithrombotic activity and lower bleeding risk. Additionally, various bioactivities of hirudin have been reported as well, including wound repair effect, anti-fibrosis effect, effect on diabetic complications, anti-tumor effect, anti-hyperuricemia effect, effect on cerebral hemorrhage, and others. Therefore, by collecting and summarizing publications from the recent two decades, the pharmacological activities, pharmacokinetics, novel preparations and derivatives, as well as toxicity of hirudin were systematically reviewed in this paper. In addition, the clinical application, the underlying mechanisms of pharmacological effects, the dose-effect relationship, and the development potential in new drug research of hirudin were discussed on the purpose of providing new ideas for application of hirudin in treating related diseases.